A guide to film and TV cosplay - Swinyard, Holly (White Owl, an imprint of Pen & Sword Books Ltd., 2021)
"Cosplay is a hobby that is sweeping the globe, you can see it at comic cons, book launches, movie screenings and even on popular TV shows... A mix of exciting craft skills, heady escapism and passion for pop culture, it's easy to see why cosplay has become so popular with people no matter who they are, because now they can be anyone they want, and so can you...Learn about the history of the hobby (it's been around longer than you'd think!), get your head around picking you're first costume, find out how about all the amazing skills people are using to make these costumes, and perhaps even try a few yourself."--Back cover.